Children of Cambodia's killing fields : memoirs by survivors - Dith Pran, 1942-2008; DePaul, Kim (New Haven, Conn. : Yale University Press, 1997)
"This extraordinary book contains eyewitness accounts of life in Cambodia during Pol Pot's genocidal Khmer Rouge regime from 1975 to 1979, accounts written by survivors who were children at the time. The memoirs were gathered by Dith Pran, whose own experiences in Cambodia were so graphically portrayed in the film The Killing Fields." "These testimonies bear shattering witness to the slaughter committed by the Khmer Rouge. The contributors - most of them now living in the United States and pictured in photographs that accompany their stories - report on life in Democratic Kampuchea as seen through children's eyes. They speak of their bewilderment and pain as Khmer Rouge cadres tore their families apart, subjected them to brainwashing, drove them from their homes to work in forced-labor camps, and executed captives in front of them. Their stories tell of suffering, the loss of innocence, the struggle to survive against all odds, and the ultimate triumph of the human spirit."--Jacket
Songs my enemies taught me / Sophiline Cheam Shapiro -- Letter to my mother / Chath Piersath -- Worms from our skin / Teeda Butt Mam -- One spoon of rice / Youkimny Chan -- Memoir of a child's nightmare / Sopheap K. Hang -- New Year's surprize / Sreytouch Svay-Ryser-- Dark years of my life / Savuth Penn -- Jail without walls / Charles Ok -- Witnessing the horror / Moly Ly -- Unfortunate Cambodia / Sarom Prak -- Living in the darkness / Roeun Sam -- Four-year-old's view of the Khmer Rouge / Sarah P. Tun -- Tragedy of my homeland / Navy Dy -- Hurt, pain, and suffering / Ratha Duong -- Darkness of my experience / Khuon Kiv -- Survival in spite of fear / Gen L. Lee -- Pol pot / Susie Hem -- Bitter life / Ouk Villa -- Unplanned journey / Hong A. Chork -- Motherland / Vibolreth Bou -- My mother's courage / Arn Yan -- Escaping the horror / Rith Mean -- When the owl cries / Chanrithy Him -- End of childhood / Seath K. Teng -- My sadness / Darith Keo -- Life in Communism / Dave Lonh -- Nightmare / Hamson C. Taing -- Imprinting compassion / Sophea Mouth -- Tonle Sap Lake Massacre / Ronnie Yimsut.
Includes bibliographical references (page 195).
Print version record.
English.
JSTOR
Keywords: Cambodia -- History -- 1975-1979.; Political atrocities -- Cambodia; Children -- Cambodia -- Biography; Cambodge -- Histoire -- 1975-1979.; Atrocités politiques -- Cambodge; HISTORY; Children; Political atrocities; Cambodia; 1975-1979; Biography; Biographies; History; Biographies; Biographies